Risk factors of coronary heart disease in children and young adults with parental history of premature coronary heart disease - Murti Andriastuti; Sudigdo Sastroasmoro; Agus Firmansyah (Indonesian Pediatric Society, 2003)
Background Morbidity and mortality of coronary heart disease(CHD) are recently increasing. This is related to changes in lifestyle,such as lack of activity and high consumption of fatty diet. Themain cause of CHD is atherosclerosis. The development of ath-erosclerosis takes a long time, is asymptomatic, and might beginin childhood. The important risk factors that have roles in increas-ing the likelihood of atherosclerosis are family history of prematureCHD, hypertension, hyperlipidemia, obesity, smoking and irregu-lar activity.Objective The aim of this study was to find out the prevalence ofCHD risk factors in children and young adults who had parentalhistory of premature CHD.Methods This was a descriptive cross sectional study conductedon offspring of premature CHD patients who were admitted in theintensive cardiology care unit (ICCU) of Cipto MangunkusumoHospital between January 1999 to December 2001 and of prema-ture CHD patients who visited the Cardiology Clinic of the Depart-ment of Internal Medicine, Cipto Mangunkusumo Hospital duringMarch and April 2002. Subjects were aged 12 to 25 year-old.Results Among the subjects, 40% had hyperlipidemia, 8% hadhypertension, 11% were obese, 21% were active smokers, 41%were passive smokers, and 73% had irregular activity. Ninety-sevenpercents subjects had more than 1 risk factors.Conclusions The prevalence of hyperlipidemia, hypertension,obesity, passive smoker, active smoker and irregular activity inchildren and young adults with parental history of premature CHDin this study were higher than those in the normal population.Most had more than 1 risk factor, increasing the likelihood of CHD.A screening test should be performed on children with parentalhistory of premature CHD so that early preventive measures mightbe done to minimize the risk factors